Detecção do peptídeo p17 (HIV) baseado em SERS (Surface-enhanced Raman Spectrosocpy) - Carneiro, Leandro de Bispo [UNESP] (2015)
Surface-enhanced Raman Scattering (SERS) technique offers great promises for simplified and sensitive detection of biomolecular interactions that are relevant for early disease diagnostics. Human immunodeficiency virus (HIV) has been a problem for decades. There are several methods of diagnostics based on antibodies specific reactions, such as enzyme-linked immunosorbent assays (ELISAs) and rapid test (RT). However, new strategies have been developed for rapid HIV diagnostics and, as a proof-of-concept, peptide p17-1 was considered here. The matrix protein p17 is a structural protein that is essential in the life cycle of the retrovirus The early stages of the virus replication involve the pre integration of the DNA complex into the nucleus P17 plays a role in RNA viral binding and transport to the membrane. Here were describe two new SERS platform for HIV detection based on peptide p17-1 (sequence LSGGELDRWEKIRLPGG). The antibody anti-p17 was immobilized in a planar gold surface using two differents self-assembled (SAM) techniques. First SAM, were obtained by immersion of the surface into ethanolic solution of 11-Mercaptoundecanoic acid (MUA). Second SAM were obtained by immersion in aqueous solution aquous mixtures of (SH-PEG-COOH/SH-PEG-CH3) and polyethylene glycol (PEG,). Here were describe the two platforms as SAM-MUA and SAMPEG, respectively. Both SAM's were immersed in a solution containing the anti-p17. Samples at this step were called capture platform-MUA and capture platform-PEG. Both capture platforms were funcionalizated with the peptide p17-1. SERS probes were prepared with gold nanoparticles coated with a Raman reporter molecule (Nile Blue A) and, functionalized with an anti-p17. These structures (SERS probe and capture platforms) allow for a sandwich assay, a strategy regularly used for high-sensitivity detection. The light blue color in the SERS mapping represents peptide strong...